1013 RADIOFREQUENCY CATHETER ABLATION OF IDIOPATHIC VENTRICULAR FIBRILLATION: A CURRENT SINGLE-CENTRE EXPERIENCE. (15th December 2022) - Boccellino, Antonio; Napolano, Antonio; Negro, Gabriele; Giannelli, Luigi; Calovic, Zarko; Vicedomini, Gabriele; Rondine, Roberto; Ballarotto, Marco; Maiolo, Vincenzo; Sabatelli, Ludovico; Ciconte, Giuseppe; Pappone, Carlo
Abstract: Short-coupled idiopathic ventricular fibrillation (SC-IVF) is a rare, life-threatening arrhythmia, accountable for 5–10% of out-of-hospital cardiac arrests (OHCA). Catheter ablation of the short-coupled premature ventricular contraction (PVC) that triggers VF has been shown to prevent VF recurrences in outdated case series. Aim: To evaluate the clinical outcome and summarize the recent experience of 3D electrophysiological mapping and radiofrequency catheter ablation (RFCA) of SC-IVFs in a tertiary high-volume referral centre. Methods: from January 2016, we enrolled all consecutive patients diagnosed with SC-IVF and treated by RFCA. Structural heart disease was excluded in all patients by means of echocardiography, cardiac magnetic resonance, coronary angiography, and exercise test. Brugada syndrome and long QT syndrome were excluded by Ajmaline and Epinephrine tests, respectively. The CARTO system was used to construct detailed 3D electroanatomic maps of the right and left ventricle. Mapping and ablation were performed with a standard 3.5- irrigated tip catheter. The PVCs were localized by mapping the earliest bipolar electrogram relative to the onset of the ectopic surface QRS (confirmed by QS complex in the unipolar configuration). Pace mapping was used in patients with infrequent PVCs. The origin of PVCs from fascicles/Purkinje network was indicated by initial sharp potentials preceding the ectopic QRS complex. The procedural end point was the abolition of all clinical PVCs. Outcome (freedom from SC-PVCs and VF episodes) was assessed by Holter monitoring and defibrillator memory interrogation. Results: eleven consecutive patients [8 men, 3 women; median age 41 (± 5 years)] were enrolled. 10/11 patients (91%) were asymptomatic prior the index VF event, while 1 patient (9%) experienced recurrent syncope. An aborted OHCA was the index event in all patients. Arrhythmic storm was observed at the index presentation in 2 patients (18%). No patient had family history of sudden cardiac death. All patients were implanted with an ICD after the index event. The delay in SC-IVF diagnosis was 3 (± 2 years) from the index event. 2 patients (18%) had ≥ 2 SC-PVC morphologies. The mean coupling interval (CI) of the SC-PVCs ranged from 230 to 330 msec (mean 303 ± 26 msec). The CI/QT ratio ranged from 0.6 to 1 (mean 0.81 ± 0.15). 10 patients underwent RFCA for recurrent VF/ICD shocks and 1 patient for refractory electrical storm. RFCA was based on activation mapping, pace-mapping, and both in 1 (9%), 1 (9%), and 9 (82%) patients, respectively. The sites of ablation were LV Purkinje, RV Purkinje, RV non-Purkinje (RV outflow tract and tricuspid annulus), and LV non-Purkinje (LV Summit) in 3 (27%), 4 (36%), 3 (27%), and 1 (9%) patient, respectively. The first ablation was acutely successful in all patients. 1 patient experienced recurrence of SC-PVCs and VF episodes after 5 days from the first ablation and underwent a second RFCA. There were no peri-procedural complications. After a median follow-up of 22 months (ranging from 6 to 39 months) all patients were free from sustained ventricular arrhythmia recurrences: 10 patients (91%) were free from VF and PVCs; 1 patient (9%) had recurrent SC-PVCs without VF episodes. Conclusions: this retrospective study explored the effectiveness of RFCA combined with the advanced electroanatomic mapping in a current cohort of patients with history of OHCA diagnosed with SC-IVF. RFCA of SC-PVCs was safe and highly effective in abolishing VF episodes in all patients.